Evaluating drivers impacting buyer-supplier relationships in agile supply chain / Nazura Mohamed Sayuti …[et al.] - Mohamed Sayuti, Nazura; Mohd Arifin, Azitadoly; Mohamad Arshad, Afiza Azura; Shafinaz, Azlin (Universiti Teknologi MARA Cawangan Selangor, 2017)
This study identifies the critical drivers of buyer-supplier relationships in the context of agile supply chains. It develops a conceptual framework consisted of three higher level constructs and eleven determinants of buyer-supplier relationship. Data and information were collected through in-depth interviews from senior managers of six MNC’s (buyers) and six local SMEs (suppliers) operating in electrical and electronics industry in Malaysia. AHP, a multi-criteria-decision-making methodology, was used to analyze data and access the criticality of determinants. The results indicate that SMEs regard partner’s characteristics capability as the most important construct, whereas MNCs consider process capability as most important construct in building a buyer supplier relationship. The results also indicate that the determinants such as resources complementarities and partner capabilities are more important for SMEs, whereas flexibility proficiency and information technology determinants are more important for MNCs. The findings of this study may generate ideas to manufacturers in agile environment to focus on partner’s expectations in developing a mutually beneficial relationship.